Relationship of traumatic brain injury to chronic mental health problems and dementia in military veterans. (10th August 2019) - Elder, Gregory A.; Ehrlich, Michelle E.; Gandy, Sam
Highlights: TBI caused by blast exposure is relatively unique to the military. Separating mild TBI from post-traumatic stress disorder is difficult. TBI is a risk factor for the development of neurodegenerative diseases. TREM2 and TYROBP/DAP12 link inflammation and microglia to AD and possibly TBI. Abstract: Traumatic brain injury (TBI) is an unfortunately common event in military life. The conflicts in Iraq and Afghanistan have increased public awareness of TBI in the military. Certain injury mechanisms are relatively unique to the military, the most prominent being blast exposure. Blast-related mild TBI (mTBI) has been of particular concern in the most recent veterans although controversy remains concerning separation of the postconcussion syndrome associated with mTBI from post-traumatic stress disorder. TBI is also a risk factor for the development of neurodegenerative diseases including chronic traumatic encephalopathy (CTE) and Alzheimer's disease (AD). AD, TBI, and CTE are all associated with chronic inflammation. Genome wide association studies (GWAS) have identified multiple genetic loci associated with AD that implicate inflammation and - in particular microglia - as key modulators of the AD- and TBI-related degenerative processes. At the molecular level, recent studies have identified TREM2 and TYROBP/DAP12 as components of a key molecular hub linking inflammation and microglia to the pathophysiology of AD and possibly TBI. Evidence concerning the relationship of TBI to chronic mental health problems and dementia is reviewed in the context of its relevance to military veterans.